The Universal Patterns of Leadership - Lebese, Mokone, Solomon (My University, 2022)
Principles are fundamental truths that serve as the foundation for systems of belief, behavior or for a chain of reasoning. It is this understanding that has led the author to look at principles, systems and patterns that are the bedrock of behavior for all creatures in the universe. It is not the behaviors of living creatures only but the behavior of all creation. An examination of the universe leads one to note that there are patterns that govern everything. Those patterns were not a fabrication of man but preceded him. These patterns or systems enhance goal achievement and survival of everything. The systems and patterns are like a road that travelers use as they journey to their desired destination. Noncompliance to the pattern direction is disastrous. The patterns are myriad in order to serve myriad needs of elements in the universe. Essentially, the patterns are meeting a need of their clients or users. Users are mandated by the system or pattern to comply or obey. In a sense, this compliance could be described as adaptation. Since leadership is the concept to be examined, one observes that the leadership situation is a system or pattern that the emerging leader must understand and follow through wherever and whenever the pattern mandates. The reader is therefore invited to study carefully the patterns exhibited all around him and develop skills to navigate, maneuver and practice. The reader must read to comprehend and be willing to accept the presented mandate as shown in the patterns; once understood, practice must follow in order not to be at variance with the identified pattern or system. The reader is now compelled to develop three competencies to survive in this systemic universe where he is, namely: Foundational competence, Practical Competence and Reflective Competence. These three competencies are abilities developed in the process of development and growth. Without understanding the mandate, it follows that nothing will be done and when nothing is done, ownership of the idea will not be realized. That individual, with no competence, cannot be identified with the idea exhibited by the pattern. No ownership implies no positive development and without positive development, immaturity is perpetuated. This immaturity is also development in the opposite direction. Enjoy the universal pattern discovery as you learn the ropes of dynamic leadership.
Keywords: Behaviour; Leadership; SAQA; Situation; Universal Patterns